Operative Choice for Length-Unstable Femoral Shaft Fracture in School-Aged Children: Locking Plate vs. Monolateral External Fixator - Hong, Pan; Rai, Saroj; Tang, Xin; Liu, Ruikang; Li, Jin (Frontiers in Pediatrics, 2022)
Background: Locking plate (LP) is a good choice in the treatment of length unstable femoral shaft fracture in children. Monolateral external fixator (EF) has been reported for this condition for decades. This study aims to compare the clinical outcomes of school-aged children with length unstable femoral shaft fracture treated with LP vs. EF. Methods: Patients aged 5-11 years old with length unstable femoral shaft fractures treated at our institute from January 2014 to January 2018 were retrospectively reviewed and categorized into LP and EF group. The preoperative data, including baseline information of the patients, radiographic parameters, and types of surgical procedure, were collected from the hospital database, and postoperative data, including complications, were collected during the follow-up visits. Results：In all, 36 patients (average, 8.2 ± 2.1 years; male 20, female 16) in the LP group and 35 patients (average, 8.3 ± 2.3 years; male 20, female 15) in the EF group were included. There was significantly less operative time for EF (45.4 ± 7.8 min) as compared with LP (67.8 ± 11.3 min), P < 0.001. As for the frequency of fluoroscopy, there was a significant difference between the EF (13.9 ± 2.4) and LP (16.5 ± 3.2) group (p < 0.001). The rate of major complications was not significantly different between these two groups. There was a significant difference between the EF group (11.2 ± 5.8, mm) and the LP group (7.5 ± 1.6, mm) group concerning limb length discrepancy, P < 0.001. Conclusion：Both LP and EF produce satisfactory outcomes in school-aged children with length unstable femoral shaft fractures. External fixation remains a viable choice without the necessity of secondary surgery for hardware removal.